Responsible and ethical application of artificial intelligence systems in healthcare through a case study in diagnostics and personalized medicine - Milovanović, Dragorad (Napredak, 2024)
The paper discusses new challenges of responsible and ethical application of artificial intelligence (AI) systems in healthcare. Academic research and commercial development focused on medicine are showing exponential growth; however, regulatory requirements for clinical use and commercial introduction are progressing more slowly. After classifying AI applications and identifying challenges and risks, a case study in diagnostics and personalized medicine is presented. The main result is a clear overview of the upcoming trends in medicine that can help legislators prepare to create new regulations and ethical principles of practice for new AI technologies. It is essential that technical experts, policy makers, legislators and other decision-makers accept responsibility.
Keywords: artificial intelligence; regulation; case study; medicine